Reconceptualizing Hifz al-Bīʻah within Maqāṣid al-Sharī'ah: An Islamic Environmental Jurisprudence Analysis of Forest and Land Fires in Kalimantan - Muhammad Ramsah; Ahmad Dakhoir; Puji Rahmiati (Mir'ah: Family Law and Legal Culture, 2026)
Forest and land fires (FLF) remain a recurring environmental problem in Kalimantan, causing ecological degradation, public health risks, economic losses, and climate-related impacts. This study aims to analyze FLF from the perspective of environmental Islamic jurisprudence (fiqh al-bīʻah) by positioning ḥifẓ al-bīʻah (environmental preservation) as a contemporary development of maqāṣid al-sharī’ah. This research employed a descriptive qualitative library research method by examining the Indonesian Council of Ulama (MUI) Fatwa No. 30 of 2016, MUI Fatwa No. 86 of 2023, Islamic legal maxims, maqāṣid al-sharī’ah literature, and secondary data on FLF in Kalimantan during 2023–2024. The findings reveal that land clearing through burning contradicts the principle of ḥifẓ al-bīʻah and is declared prohibited (haram) under both fatwas. Islamic legal maxims, including (Lā dharara wa lā dhirāra), (Dar'ul mafasidi muqaddamun 'ala jalbil mashalih), and (Ad-dhararu yuzalu) further emphasize that preventing environmental harm must take precedence over short-term economic interests. This study contributes to strengthening environmental Islamic jurisprudence as a normative framework supporting FLF prevention through the integration of state regulations, religious fatwas, and environmental da'wah. Nevertheless, this study is limited to library research; therefore, future field-based studies are needed to examine the implementation of ḥifẓ al-bīʻah in forest and land fire prevention.